ChemInform Abstract: Density and Viscosity Study of Solvents, Mixture of Solvents with or without Additives: A Mini Review. Issue 51 (17th December 2013) - Shafique, Mohd.; Asif, Syed; Abed, Syed; Pradhan, Vidya; Farooqui, Mazhar
Abstract Review: 59 refs.